2010
DOI: 10.1002/ijc.25416
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 is essential for the maintenance of neurosphere‐initiating tumor cells in patients with glioblastomas: A potential for targeted therapy?

Abstract: Glioblastoma (GBM), the highest-grade form of gliomas, is the most frequent and the most aggressive. Recently, a subpopulation of cells with stem cells characteristics, commonly named ''tumor-initiating stem cells'' (TISCs) or ''cancer stem cells'' (CSCs) were identified in GBM. These cells were shown to be highly resistant to chemotherapeutic drugs and to ionizing radiations. Consequently, the knowledge of the signals that regulate the functions and survival of TISCs is crucial. In our work, we describe a neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
94
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(100 citation statements)
references
References 56 publications
6
94
0
Order By: Relevance
“…34 Villalva et al further indicated that stem cells derived from GBM expressed a constitutively phosphorylated STAT3, which was essential for the proliferative and the self-renewal capacity. 35 Thus, STAT3 activation appears as a common feature of CSC-GBM. Furthermore, ObR had full signaling capabilities and was able to activate the JAK/STAT3 pathway, the major pathway used by leptin to exert its effects.…”
Section: Discussionmentioning
confidence: 99%
“…34 Villalva et al further indicated that stem cells derived from GBM expressed a constitutively phosphorylated STAT3, which was essential for the proliferative and the self-renewal capacity. 35 Thus, STAT3 activation appears as a common feature of CSC-GBM. Furthermore, ObR had full signaling capabilities and was able to activate the JAK/STAT3 pathway, the major pathway used by leptin to exert its effects.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a growing body of recent evidence gathered using a variety of different small molecules that indirectly inhibit STAT3 by targeting upstream molecules such as the JaK family members 6 strongly suggest that STAT3 signaling is crucial for the survival and proliferation of BTSCs and GBM both in vitro and in vivo. 7 However, because of their broad targeting nature, these drugs have limited translational potential due to numerous side effects. Hence, drugs with the ability to more specifically block STAT3 activity may provide effective treatment of GBM.…”
mentioning
confidence: 99%
“…The STAT3 signaling pathway is associated with TMZ chemoresistance in GBM, but the underlying mechanisms are unclear (Villalva et al ., 2011). Here, we show that RXFP1 agonist CTRP8 (Glogowska et al ., 2013) mitigated the ability of first‐line GBM drug TMZ to induce DNA damage.…”
Section: Resultsmentioning
confidence: 99%